2009
DOI: 10.1007/978-1-60327-029-8_12
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Effective and Safe Removal of Membrane Cholesterol from Lipid Rafts in Vascular Endothelial Cells: Implications in Oxidant-Mediated Lipid Signaling

Abstract: Lipid raft-associated cholesterol has been identified as a pivotal player among membrane lipids in regulating cellular functions. Cholesterol of the vascular endothelial cell (EC) membranes is also being recognized as an important element in the vascular EC signaling. However, methods utilized in studying the important role of lipid raft-associated cholesterol in cell signaling involve removal of the raft cholesterol with the aid of chemical agents called cyclodextrins. Caution should be exercised in using cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…Thus, the present study focused on the effects of another important lipid raft component, cholesterol, in the context of breast cancer. HP-β-CD can deplete cholesterol in lipid rafts and this may affect the construction of lipid rafts and then cancer cell viability by regulating the transmembrane signaling (15,27). For example, Alawin et al (28) found that antiproliferative effects of γ-tocotrienol are associated with lipid raft disruption in HER2-positive human breast cancer cells and Badana et al (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the present study focused on the effects of another important lipid raft component, cholesterol, in the context of breast cancer. HP-β-CD can deplete cholesterol in lipid rafts and this may affect the construction of lipid rafts and then cancer cell viability by regulating the transmembrane signaling (15,27). For example, Alawin et al (28) found that antiproliferative effects of γ-tocotrienol are associated with lipid raft disruption in HER2-positive human breast cancer cells and Badana et al (29).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study sought to explore the effects of the change in cholesterol in lipid rafts in the development of EMT regulated by the TGF-β/Smad signaling pathway. Toward accomplish this, hydroxypropyl-β-cyclodextrin (HP-β-CD) was used for in vitro treatment of MDA-MB-231 cells to deplete cholesterol in lipid rafts (15).…”
Section: Introductionmentioning
confidence: 99%
“…C-Laurdan imaging was performed with and without treatment with sterol-specific drugs MBCD and Amphotericin B (Amp B), which respectively target cholesterol 50 – 52 and ergosterol 53 . Both MBCD and Amp B have been used extensively in previous investigations of lipid rafts 51 , 52 , 54 57 .…”
Section: Resultsmentioning
confidence: 99%
“…These results could indicate that free polymer aids in endosomal escape of siRNA formulations, which intern, aids gene knockdown and was particularly noticed with the cyclodextrin analogs. We speculate that the known affinity for cyclodextrin to extract cholesterol from cell membranes 36-39 could play a role in aiding endosomal disruption and polyplex release into the cytoplasm with the CD4 polymer series.…”
Section: Discussionmentioning
confidence: 99%